Analisis Kebiasaan Belajar Mahasiswa yang Aktif Organisasi Maupun Bekerja dengan IPK Cumlaude di Perguruan Tinggi Jakarta dan Depok - Citra Febriyanto, Fery; Ibnatur Husnul, Nisak Ruwah (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
This study aims to determine the study habits of students who are active in organizations and works with a GPA of 3.75 (cumlaude) in universities in Jakarta and Depok. The research method used a descriptive qualitative. The subjects of this research were 12 students, i.e. four students were each from the UI, UNJ, AL-Azhar and UNPAM campuses. The selection of sources was categorized as students having a GPA of 3.75 while working or being active in organizations. The instrument used was an interview guide validated by a reviewer and the data collection technique was through interviews. The data analysis technique used source triangulation technique. The results of the study founded that students who studied while working or participating in an organization with a GPA of 3.75 had learning habits such as the followings: 1) Students must have good time management in utilizingÂ soft skillsÂ andÂ hard skillsÂ by setting a priority scale in the learning process, active organization and work.Â 2) Students must create habits with certain patterns for the goals toÂ beÂ achieved, by adjusting each individual’s ability to study, organize and work.Â 3) Students must know the strengths and weaknesses of each to find outÂ whatÂ supports and hinders the learning process, organization or work.